Impact of anthropogenic and climatic factors on forest structure in and around the Muanda mangrove Marine Park in DR Congo - Soloum Clément, Teteli; Kokouvi Buno, Kokou; Molo Jacques, Elangilangi; Mugisho Serge, Mukotanyi; Joel Lopa, Lobho; Alioune Badara, Diop (Revue Ecosystèmes et Paysages, 2024)
The study highlights the impact of global change on forest structure within and around the Muanda mangrove marine park in RD Congo, focusing on key forest structure parameters such as species composition, basal area, tree height, and Leaf Area Index (LAI). This study assessed forest structure parameters in and around the park and linked between forest structure to global change. Forest structure parameters, namely species composition, basal area, tree height and Leaf Area Index (LAI), were measured at 5 sites. Analyses showed significant variation in mean height between the different sites, in the order of 22m, 25m and 30m for the marine sites, and 7m and 10m for the terrestial sites. The mean basal area of trees varied from 52 m2. ha-1 to 15 m2.ha-1. Two undisturbed mangrove sites have the highest basal area, the lesser disturbed sites have the average basal area and the degraded sites have the lowest basal area. The carbon stock capacity shows the same trend. The highest average LAI is 3.79. The lowest is 1.08. Within the same site, there is a certain homogeneity of LAI values for undisturbed sites, whereas the variability of these values is high for degraded sites. In other words, forest structure parameters vary from one area of the park to another for reasons related to human activities and climate change. The existence of a link between forest structure and global change is evident.